REVIEW OF ASPECTS OF THE TRANSFER PRICING METHOD AT THE COCA-COLA COMPANY RELATED TO THE EMBEDDED ROYALTY ON THE SALE OF CONCENTRATES (CASE STUDY ON UNITED STATES COURT JUDGMENT) - Hariyanto; Fathoni, Ahmad (Jurnal Magister Akuntansi Trisakti, 2024)
The Australian Tax Office (ATO) imposed withholding tax on what is considered an Embedded Royalty implied in the purchase transaction of Pepsi Australia's concentrate to Pepsi Singapore based on the United States Tax Court Judgment Number 31183-15 where the Internal Revenue Service (IRS), the Tax Authority in America, won the case against The Coca Cola Company by correcting the subsidiary's profit level using a fair price level approach to the profits of other independent bottling companies. The purpose of this study is to examine the court's Judgment can have direct implications for companies that produce Coca-Cola drinks in Indonesia. the research method used is qualitative with a literature study, namely by analyzing books, documents, news articles, national and international journals, and laws that are directly related to the research theme. This research concludes that the purchase of concentrate contains Embedded Royalty which can be subject to Income Tax Article 26 of the Income Tax